High-performance overall water splitting based on amorphous iron doped cobalt tungstate via facile co-precipitation. Issue 15 (6th April 2021) - Wu, Jin; Xie, Renjie; Hu, Xiangchen; Nie, Zhiwei; Shi, Yanuo; Yu, Yi; Yang, Nan
Abstract : The as-prepared amorphous Fe-doped CoWO4 bifunctional electrocatalyst shows a low overpotential of 259 and 118 mV to reach a current density of 10 mA cm −2 for the OER and HER in 1 M KOH, respectively. Abstract : Exploring high-performance and low-cost bifunctional electrocatalysts is crucial for developing highly efficient overall water splitting cells. In this work, a facile and cheap co-precipitation method, which is compatible with large-scale production, is applied to prepare amorphous Fe-doped CoWO4 bifunctional electrocatalysts. Low overpotentials of 259 and 118 mV to reach a current density of 10 mA cm −2 for the OER and HER in 1 M KOH are found, respectively. Moreover, no detectable potential decay is observed at 50 mA cm −2 for at least 15 h, revealing its excellent long-term stability. Finally, a highly efficient overall water splitting cell is assembled with amorphous Fe-doped CoWO4 as a bifunctional electrocatalyst. A low cell voltage of 1.55 V is required to achieve a current density of 10 mA cm −2, which surpasses the benchmark IrO2 ‖Pt/C cell.